Desempenho de sementes de soja revestidas com biopolímeros - Scarsi, Marina (2015)
The use of biopolymers that help to fix pesticides efficiently and degrade easily without harming the environment, and still improve the physiological performance of field soybean seed may bring contributions to the soybean yield. This study aimed to evaluate the effect of cassava starch polymers (AM), sodium alginate (ALG) and polyvinyl alcohol (PVOH), in the concentrations 2, 4 and 6 g / 100 ml of solution, in the physiological attributes of seeds soy, seed speed soaking and performance of soybean seeds after three months of storage. The soybean variety used was the NK 7059 RR. The experimental design used for the three studies was a factorial with 48 experimental units: 3 polymers (AM, ALG and PVOH), 4 different concentrations (0%, 2%, 4% and 6%), with four replications, in a completely randomized design. It was observed the level of significance of the factors and their interactions, applying the test F. The polymers were evaluated by the Tukey test at 5% probability, and the concentrations were evaluated by polynomial regression. The witness obtained better results for most variables studied. Among the polymers, the best coating was observed PVOH because it was the less viscous polymer and visually not served as a substrate for microorganisms. However, also, satisfactory results were obtained for the AM and ALG polymers at a concentration of 2%. There was not interference of the polymers studied with regard to reduction of imbibition rate of soybean seeds. The hydrophilicity of polymers, mainly the AM and ALG accelerated soaking seeds harming germination at concentrations 4% and 6%. In general, the higher the concentration of polymers tended to worse results.